Use of porcine acellular dermal matrix following early dermabrasion reduces length of stay in extensive deep dermal burns. Issue 3 (May 2016) - Guo, Zhi-Qian; Qiu, Le; Gao, You; Li, Jin-Hu; Zhang, Xin-He; Yang, Xin-Lei; Peszel, April; Chen, Xu-Lin
Highlights: Assess the impact of early dermabrasion combined with porcine ADM in extensive deep dermal burns. Early dermabrasion and ADM accelerates wound healing and reduces length of hospital stay. An improvement of the scar was found in early dermabrasion and ADM group. Abstract: Objective: Extensive deep partial-thickness burns still seriously challenge the surgeon's abilities. This study aimed to assess the impact of early dermabrasion combined with porcine acellular dermal matrix (ADM) in extensive deep dermal burns. Methods: From September 2009 to September 2013, a total of 60 adult patients sustained greater than 50% total body surface area (TBSA) burn by hot water or gas explosion were divided into three groups based on dermabrasion: group A (early dermabrasion and porcine ADM), group B (early dermabrasion and nano-silver dressings), and group C (conservative group). The wound healing time and length of hospital stay were analyzed. Scar assessment was performed at 3 and 12 months after the injury with a modified Vancouver Scar Scale linked with TBSA (mVSS-TBSA). Results: No significant difference was found in mean burn size, burn depth, age, male-to-female ratio, or incidence of inhalation injury between the patients in the three groups ( p > 0.05). Compared with groups B and C, the patients that received early dermabrasion combined with porcine ADM had a shorter wound healing time ( p < 0.01). The burn patients treated with early dermabrasion and porcine ADM coverage had a mean length of hospital stay of 28.3 days (±7.2), which was significantly shorter than that of groups B and C ( p < 0.05–0.01). The mVSS-TBSA of patients in group A was significantly improved in comparison with groups B and C at 3 and 12 months after the injury. There was no significant difference in the mortality rate between the three groups ( p > 0.05). Conclusion: Early dermabrasion combined with porcine ADM coverage facilitates wound healing, reduces the length of hospital stay, and improves esthetic and functional results in extensive deep dermal burns with burn size over 50% TBSA.